PEMBELAJARAN SENI TARI DI SMP NEGERI 1 BATANGAN KABUPATEN PATI (Universitas Negeri Semarang, 2013)
This study aims to identify and describe the process of learning the art of dance in the subjects of art and culture in SMP N egeri 1 Pati Bars Bars district. This study used a qualitative approach, the target location peneletian in SMP Negeri 1 Pati Bars district. Data analysis techniques by reducing, presenting data and infer all the information correctly. The results in the learning process SMPN1 dance bars in the teaching and learning activities to implement the learning stages such as preparation, delivery, training, and performance. Dance teachers implementing these stages in order to improve student learning outcomes and the effectiveness of the time. The factors that affect the learning process of dance is a factor suppor ting and inhibiting factors. From the results of the research described the conclusion can be drawn in the learning process SMPN1 Bars activities include the activities of the learning process, preliminary, activities, core and cover. In addition, teacher s also use audio-visual media like Laptop, LCD, Projectors and VCD Cassette Dance. Suggestions relating to the process of learning the art of dance culture in SMP eri 1 District Bars Bars are For teachers in the use of audio -visual media enhanced user creativity, so that students do not feel bored at dance lessons. Infrastructure needs plus room art glass wall, in order to facilitate the students in the dance practice. Students are expected to have their own dance VCD, so can be used for self -study.